(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Despite the centrality of motherhood in African and biblical worldviews, scholarly engagement with its symbolic and philosophical representations across cultures remains relatively underexplored. The study, therefore, interrogates the cultural constructions and ideological representations of motherhood in Hebrew and Yoruba proverbial traditions. Data were purposively selected from Yoruba proverbs and the biblical text of Proverbs 31:10-30. Anchored in Catherine Acholonu’s Motherist theory and employing qualitative content analysis, the study examines how both traditions encode the ethics, aesthetics, and social philosophy of motherhood. The findings reveal the universality of proverbial expressions in expressing the moral and socio-cultural values associated with mothers. Both the Hebrew and Yoruba traditions valorise the mother as a virtuous, industrious and self-sacrificing figure whose wisdom and resilience are central to familial survival and communal stability. The persona in Proverbs 31 finds her parallel in the archetypal African mother who embodies love, tolerance and cooperation in contrast to the confrontational ethos of radical feminism. Like her African counterpart, she achieves empowerment not through antagonism but through industriousness, moral fortitude and spiritual agency. The study concludes that Motherism offers a transformative paradigm that transcends gender polemics by proposing a humanistic, inclusive, and communitarian model of gender relations grounded in complementarity, mutual respect, and social harmony.